Thiosulphate driven autotrophic denitrification via nitrite using synthetic wastewater. Issue 6 (18th February 2021) - Statiris, Evangelos; Hadjimitsis, Evanthis; Noutsopoulos, Constantinos; Malamis, Simos
Abstract: BACKGROUND: The removal of biological nitrite from wastewater can occur by both heterotrophic and autotrophic bacteria. Autotrophic denitritation can be implemented by using different sulphur forms (e.g., S 2−, S 0 or S₂O₃ 2− ) as electron donors, and there is no need for organic carbon availability, as is required in heterotrophic denitrification. This work investigated an alternative biochemical pathway for nitrite removal from synthetic wastewater with high nitrite content, using thiosulphate as electron donor. The process was examined for 170 days in three identical 1 L sequencing batch reactors (SBR) that were inoculated with filtrate originating from the aerobic filters of the desulphurization unit of a wastewater treatment plant (WWTP). RESULTS: The SBR units were able to remove approximately 98% of the initial nitrite concentration of 70–80 mg N L −1, operating under an HRT of 5d. The batch experiments showed autotrophic denitritation rates (NUR) with average values between 0.91 and 1.50 mg NO₂‐N gVSS −1 h −1 during the whole duration of the experiment, with a remarkable increase on the NUR after the initial lag time of the process, where rates of up to 4.74 mg NO₂‐N gVSS −1 h −1 were measured. CONCLUSION: The daily monitoring of the three SBR units showed that denitritation via thiosulphate can be effective enough for nitrite removal without carbon source addition. The lag phase of the process, as well as the loss of alkalinity and pH drop during denitritation, are disadvantages that can be counterbalanced with the cost savings resulting from not needing a carbon source addition when treating wastewater with low C/N ratio. © 2021 Society of Chemical Industry